Development of Cardiopulmonary Resuscitation Pillows for Increasing Number of Bystanders CPR In Lubuklinggau City - Wijaya, Sapondra; Wibowo, Wahyu Dwi Ari; Susmini, Susmini; Soewito, Bambang (International Journal of Nursing and Health Services (IJNHS), 2023)
Introduction: Cardiac arrest is a situation that can lead to death if CPR is not immediately assisted. The chances of survival increase if the victims are directly helped by people nearby or CPR bystanders rather than waiting for the medical team to arrive. Training CPR bystanders requires large resources, including expensive CPR mannequins as a simulation medium. Creativity is needed to create cheap CPR simulation media with good feasibility. Objective: The study aimed to construct and test the effect of the CPR Pillow to improve the CPR skill in Lubuklinggau, South Sumatra, Indonesia. Method: Research and Development (R&D) with experimental tests, pre-test, and post-tests were applied in this study. Forty people were given two meetings within two weeks. Skill was measured by how the subject performed hand's-only CPR using the CPR Operational Procedure checklist. Result: The result of this study is the creation of a low-cost CPR pillow design that meets the eligibility as a low-fidelity simulation medium for CPR skills. The data analysis using the paired t-test showed a significant effect of CPR training using CPR Pillows on the trainees' hand's-only CPR skills (t=-37,749) with a value of p=0.000. Recommendation: This CPR pillow can be used as a hand's-only CPR simulation medium. CPR simulation using this CPR pillow is a low-fidelity simulation. There is a positive influence related to CPR training using this CPR pillow on the hands-only CPR skills of the trainees